Unpacking Configurational Dynamics: Sequence Analysis and Qualitative Comparative Analysis as a Mixed-Method Design - Camilla Borgna; Emanuela Struffolino (Sequence Analysis and Related Approaches: Innovative Methods and Applications, 2018)
This chapter proposes a novel sequential mixed-method design that brings together the strengths of sequence analysis (SA) and qualitative comparative analysis (QCA). Both methods rely on an epistemological framework that combines analytical and holistic elements: they share the notion of analytically approaching social phenomena without disregarding their complexity. We apply SA as a first step to analyze the unfolding of phenomena over time. Specifically, through discrepancy analysis of state sequences, one can identify the time points when trajectories (start to) diverge from each other. In a second, explanatory step, QCA is applied to investigate whether, at such crucial time points, some particular configurations of factors are logically sufficient for the occurrence of a given state (or outcome). We provide an illustrative application to women's employment trajectories in divided Germany by using data from the Adults Cohort of the German National Educational Panel (NEPS). By preserving the analytical and holistic perspective on trajectories, our proposed design highlights the dynamic of socio-demographic factors sufficient for women to be in employment or education at critical turning points over the life course. This design takes on the challenge, summarized in Abbott's call for a `processual sociology', to investigate both the dynamics of social phenomena as lineages of successive events and the complexity of contextual characteristics of `present' moments. We conclude with an overview of research fields where our framework holds the promise of being applied fruitfully, namely life-course research, social stratification studies, policy evaluation, and comparative politics.
Keywords: 330